Aluminium and aluminium alloys. Anodizing. Assessment of quality of sealed anodic oxidation coatings by measurement of the loss of mass after immersion in phosphoric acid/chromic acid solution with prior acid treatment Part 7, (15th April 1999) - British Standards Institution,
No abstract available